SAMI3 prediction of the impact of the 21 August 2017 total solar eclipse on the ionosphere/plasmasphere system. Issue 12 (23rd June 2017) - Huba, J. D.; Drob, D.
Abstract: We present quantitative predictions of the impact of the upcoming total solar eclipse on the ionosphere and plasmasphere using the Naval Research Laboratory (NRL) model Sami3 is Also a Model of the Ionosphere (SAMI3). The eclipse will occur over the continental United States on 21 August 2017. Our simulation results indicate that in the vicinity of the eclipse (1) the total electron content (TEC) decreases by up to ∼ 5 TEC units (TECU; 1 TECU = ×10 16  m −2 ) which is a ∼ 35% decrease in TEC, (2) the electron density decreases by a factor of ∼ 50% in the F region, (3) the electron temperature decreases by up to ∼800 K in the plasmasphere, and (4) the O + velocity changes from ∼40 m s −1 upward to ∼20 m s −1 downward in the F region. Interestingly, the continental size modification of the ionospheric conductance modifies the global electric field, which should lead to measurable changes in the TEC in the southern conjugate hemisphere ( ≲ 1 TECU). Plain Language Summary: We use the first‐principles ionosphere/plasmasphere model Sami3 is Also a Model of the Ionosphere to predict the impact of the upcoming total solar eclipse traversing the continental United States on 21 August 2017. We find that the reduction in solar radiation reaching the Earth has a significant impact on the Earth's ionosphere: the electron density can decrease by almost a factor of 2 in the F region between 150 and 350 km, and the electron temperature can decrease by 15% at higher altitudes. Moreover, we find that the reduction in the electron density affects the electrical conductance of the ionosphere which modifies the global electric field in the American sector. This can modify the Earth's ionosphere in the magnetically conjugate region at the tip of South America which should be observable. Key Points: Solar eclipse will reduce the electron density in the F region by up to a factor of 2 The electron temperature in the plasmasphere will decrease by up to 15% The electron density will be affected in the magnetically conjugate hemisphere